Choledocal fasciolasis by Fasciola hepatica in surgery of chronic calculous cholecistitis - Beltrán-Fabián, María (2011)
We report a case of Fasciola hepatica in a 50 year-old woman born in Huaral, Lima, and living in Ate Vitarte, district of Lima, Peru, who was admitted because of seven days of disease characterized by progressive abdominal pain. She visited Ate’s Hospital because of right hipocondrial and epigastric cramping abdominal pain in the morning accompanied by nausea and vomiting in four opportunities. Conjunctives were slightly icteric, abdomen was distended and depressible, there was no visceromegaly, Murphy’s sign was positive, and thorax and lungs showed no alterations. At cholecistectomy three specimens identified as Fasciola hepatica were extracted. Following treatment with triclabendazole, clinical course was uneventful.